2021
DOI: 10.2147/ott.s309408
|View full text |Cite
|
Sign up to set email alerts
|

Successful Management of a Patient with Refractory Primary Central Nervous System Lymphoma by Zanubrutinib

Abstract: Primary central nervous system lymphoma (PCNSL) is a rare subtype of extranodal non-Hodgkin lymphoma, and the most frequent histological type is diffuse large B-cell lymphoma (DLBCL). Bruton's tyrosine kinase inhibitor (BTKi) has shown clinical activity in DLBCL. We herein report a 53-year-old man who presented with binocular diplopia, gait instability, dizziness and bucking. He was diagnosed with PCNSL by cranial magnetic resonance imaging (MRI) scan and brain biopsy. Next-generation sequencing (NGS) examinat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 20 publications
0
8
0
Order By: Relevance
“…Zanubrutinib has superior target effects by blocking several essential molecular pathways, including BCR signaling, BTK or B-lymphocyte kinase, Toll-like receptor (TLR) signaling and downregulating exhaustion markers, such as PD-1, TIM-3, and LAG-3 ( 30 ). Zanubrutinib could cross the BBB to exert its effect, alleviating Bing–Neel syndrome with CNS lymphoplasmacytic cell infiltration among Waldenström macroglobulinemia (WM) patients and successfully applied to refractory PCNSL case ( 32 , 33 ). Notably, emerging evidence has identified that zanubrutinib could modulate the immune system by inhibiting interleukin-2-inducible T-cell kinase (ITK) in T cells, which reduces T cell differentiation and shifting the balance of Th1/Th2 cells or enriches Th17 cell subsets.…”
Section: Discussionmentioning
confidence: 99%
“…Zanubrutinib has superior target effects by blocking several essential molecular pathways, including BCR signaling, BTK or B-lymphocyte kinase, Toll-like receptor (TLR) signaling and downregulating exhaustion markers, such as PD-1, TIM-3, and LAG-3 ( 30 ). Zanubrutinib could cross the BBB to exert its effect, alleviating Bing–Neel syndrome with CNS lymphoplasmacytic cell infiltration among Waldenström macroglobulinemia (WM) patients and successfully applied to refractory PCNSL case ( 32 , 33 ). Notably, emerging evidence has identified that zanubrutinib could modulate the immune system by inhibiting interleukin-2-inducible T-cell kinase (ITK) in T cells, which reduces T cell differentiation and shifting the balance of Th1/Th2 cells or enriches Th17 cell subsets.…”
Section: Discussionmentioning
confidence: 99%
“…As for two other BTKi currently available in China, 23 and 16 CNSL patients treated with orelabrutinib or zanubrutinib, respectively, were reported in a retrospective study, or in case series. The outcomes of these BTKi for PCNSL need to be followed-up [86][87][88].…”
Section: Bruton's Tyrosine Kinase Inhibitor (Btki)mentioning
confidence: 99%
“… 60 A successful case of refractory PCNSL treated with zanubrutinib has been reported. 61 The 53-year-old patient who developed progressive disease (PD) after two courses of HD-MTX-based regimen achieved CR after subsequent three courses of zanubrutinib plus chemotherapy. The patient received ASCT after four courses of zanubrutinib with chemotherapy, and his MRI revealed stable CR.…”
Section: Novel Therapies For Pcnslmentioning
confidence: 99%